Biomarkers in Ewing sarcoma: the promise and challenge of personalized medicine. A report from the Children’s Oncology Group - Shukla, Neerav; Schiffman, Joshua; Reed, Damon; Davis, Ian J.; Womer, Richard; Lessnick, Stephen; Lawlor, Elizabeth (Frontiers in Oncology, 2013)
A goal of the COG Ewing Sarcoma Biology Committee is enabling identification of reliable biomarkers that can predict treatment response and outcome through the use of prospectively collected tissues and correlative studies in concert with COG therapeutic studies. In this report, we aim to provide a concise review of the most well-characterized prognostic biomarkers in Ewing Sarcoma (ES), and to provide recommendations concerning design and implementation of future biomarker studies. Of particular interest and potentially high clinical relevance are studies of cell cycle proteins, sub-clinical disease, and copy number alterations. We discuss findings of particular interest from recent biomarker studies and examine factors important to the success of identifying and validating clinically relevant biomarkers in ES. A number of promising biomarkers have demonstrated prognostic significance in numerous retrospective studies and now need to be validated prospectively in larger cohorts of equivalently treated patients. The eventual goal of refining the discovery and use of clinically relevant biomarkers is the development of patient specific ES therapeutic modalities.